Monoshock compressor / Othman Al Affan Abd Rashid and Norjasween Abdul Malik - Abd Rashid, Othman Al Affan; Abdul Malik, Norjasween (School of Mechanical Engineering, 2023)
A mono shock compressor is a tool utilized for compressing the rear shock absorber of a motorcycle equipped with a single shock. This tool allows for the removal and replacement of the spring or other necessary adjustments to the suspension system. Typically, a mono shock compressor consists of clamps or jaws that attach to the upper and lower ends of the shock absorber. However, using a conventional mono shock compressor can be challenging and hazardous, as it involves compressing a powerful spring under high pressure. The objective of this project is to develop a user-friendly and portable mini mono shock compressor device. This device aims to reduce the amount of human energy required and improve safety precautions while removing the spring, thereby avoiding potential injuries. Product testing demonstrated its successful functioning, ensuring the safe compression of mono shock springs. In conclusion, all objectives have been achieved. This device is expected to benefit various parties, including manufacturers, third-party sellers, and workshops